Contextual Teaching and Learning Integrated with Character Education to Improve Student’s Motivation and Character in Concentration of Solutions Topic at Pharmacy Vocational School (Universitas Negeri Semarang, 2019)
The learning outcomes of pharmacy students in Cirebon were still lacking, as well as student’s motivation and character. The teaching strategies used by teachers were still conventional and character education has not been optimal. The purpose of this study was to determine whether there were differences in student’s motivation and character between students who were taught by integrated contextual learning with character education (experimental class) and students who were taught by conventional method (control class). The research method used was the experiment. The data analysis technique was independent sample t-test. The results of this study were (1) the tcount value for the character honesty; discipline; and responsibilities were 4.118; 3.709; and 7.950 respectively, > the ttable 2.003, it means that there was differences in the characters between the control and the experimental class; (2) the tcount value for student’s motivation was 3.506 > the ttable 2.003, it means that there was difference in student’s learning motivation between the control and the experimental class. The student’s responses toward learning in the experimental class amounted to 82.59% in the very good category. The result of this study are expected to contribute the information for education practitioners especially in vocational schools.